SISTEM JARINGAN SOSIAL NASIONAL (SJSN) INDONESIA (Studi Kasus Persepsi Mahasiswa di Semarang) - Warno, Warno (JURNAL STIE SEMARANG, 2012)
The government has been implementing programs aimed at 6 programs for the welfare of the community, namely: a) Family Hope Program (PKH) b) Health Assistance For Poor Families c) Help the poor education d) rice for the poor (Raskin) e) community targeted poverty alleviation program (PNPM) f) business credit (KUR) The six pro-people program to reduce poverty and achieve social welfare, the government is drafting a new program is a continuation of the six program which is a program that aims to ensure the needs of people nationwide who were named National Social Network Systems (Navigation), and the plan was carried out in , 2014. From the analysis using SPSS was also obtained large coefficient of determination (R ²) is equal to 56.9%, this means that the dependent variable (welfare) can be explained by the six independent variables (PKH, JAMKESMAS, BOS, RASKIN, PNPM, KUR) and the rest amounted to 43.1% influenced by variables that do not exist in the study. The program of the government is good and will be implemented as well as the implementers of the program is also receiving a good run, the results showed fairly good influence of the pro- people programs, but also to be seen there are many other factors that affect the welfare of the people outside the government program . In addition to being critical of the government is the welfare of the people themselves, depending on how people attempt to change their lives when the state provides various facilities da variety of programs but no kerjasamnya eat would be impossible to realize Pancasila is prosperity for all the people of Indonesia. Limitations of this study is that the sample taken was the perception of students Semarang so it would be better if the sample used is the recipient of pro-people programs, another limitation is that welfare dipengaruhioleh many factors, especially from internal community itself so that other factors do not enter in research can have a big impact, the latter is perceived limitations of the study sample is not necessarily able to describe the recipients of the government's pro-people programs